Diabetes Mellitus akibat Anti Psikotik pada Pasien Skizofrenia - Danang hafizfadillah; Rasmi Zakiah Oktarlina (Medula, 2021)
Schizophrenia is a mental illness with complex pathophysiology and covers various aspects such as behavioral, nerve, perception, and senses that can affect social life even disfunction at work. Schizophrenia requires a long-term treatment with anti-psychotic. The use of antipsychotics among adults and older has increased. Recent information regarding the use of antipsychotics in schizophrenic patients is associated with risk factors of cardiovascular and metabolic syndrome such as obesity, hypertension, insulin resistance, low HDL levels and high triglyceride levels. Diabetes mellitus is a syndrome of metabolic diseases characterized by chronic hyperglycemia either because the body does not produce enough insulin or because the cells do not respond to the insulin that has been produced. The numbers of type 2 diabetes mellitus is estimated to be two to three times higher in people with schizophrenia than in the general population, with a prevalence of 10% to 15%. The risk of diabetes is caused by antipsychotics which cause chronic effects of weight gain and systemic inflammation that will lead to insulin resistance, the direct effect of antipsychotic drugs on insulin action and drug-induced apoptosis of pancreatic beta cells. This article is a literature study to discuss the effects of using antipsychotic drugs in schizophrenic patients who have a role in the development of diabetes mellitus, direct and indirect effect of antipsychotics on the incidence of diabetes mellitus.